Correlation between secondary metabolites of Iris confusa Sealy and Iris pseudacorus L. and their newly explored antiprotozoal potentials - Passent M. Abdel-Baki; Moshera M. El-Sherei; Amal E. Khaleel; Essam Abdel-Sattar; Mohamed A. Salem; Mona M. Okba (BMC, 2023)
Abstract Background In the last few decades, the use of plant extracts and their phytochemicals as candidates for the management of parasitic diseases has increased tremendously. Irises are aromatic and medicinal plants that have long been employed in the treatment of different infectious diseases by traditional healers in many cultures. This study aims to explore the potential of three common Iris species (I. confusa Sealy, I. pseudacorus L. and I. germanica L.) against infectious diseases. Their in vitro antiprotozoal potency against Plasmodium falciparum, Trypanosoma brucei brucei, T. b. rhodesiense, T. cruzi and Leishmania infantum beside their cytotoxicity on MRC-5 fibroblasts and primary peritoneal murine macrophages were examined. Methods The secondary metabolites of the tested extracts were characterized by UPLC-HRMS/MS and Pearsons correlation was used to correlate them with the antiprotozoal activity. Results Overall, the non-polar fractions (NPF) showed a significant antiprotozoal activity (score: sc 2 to 5) in contrast to the polar fractions (PF). I. confusa NPF was the most active extract against P. falciparum [IC50 of 1.08 μg/mL, selectivity index (S.I. 26.11) and sc 5] and L. infantum (IC50 of 12.7 μg/mL, S.I. 2.22 and sc 2). I. pseudacorus NPF was the most potent fraction against T. b. rhodesiense (IC50 of 8.17 μg/mL, S.I. 3.67 and sc 3). Monogalactosyldiacylglycerol glycolipid (18:3/18:3), triaceylglycerol (18:2/18:2/18:3), oleic acid, and triterpenoid irridals (spirioiridoconfal C and iso-iridobelamal A) were the top positively correlated metabolites with antiplasmodium and antileishmanial activities of I. confusa NPF. Tumulosic acid, ceramide sphingolipids, corosolic, maslinic, moreollic acids, pheophytin a, triaceylglycerols, mono- and digalactosyldiacylglycerols, phosphatidylglycerol (22:6/18:3), phosphatidylcholines (18:1/18:2), and triterpenoid irridal iso-iridobelamal A, were highly correlated to I. pseudacorus NPF anti- T. b. rhodesiense activity. The ADME study revealed proper drug likeness properties for certain highly corelated secondary metabolites. Conclusion This study is the sole map correlating I. confusa and I. pseudacorus secondary metabolites to their newly explored antiprotozoal activity.